Comparison of Antioxidant and Anti-collagenase Activity of Genistein and Epicatechin - Geeta,; Widodo, Wahyu Setia; Widowati, Wahyu; Ginting, Chrismis Novalinda; Lister, I Nyoman Ehrich; Armansyah, Adek; Girsang, Ermi (Pharmaceutical Sciences and Research, 2019)
Background: Skin aging is a complex natural process caused by both intrinsic or genetically programmed aging and extrinsic aging caused by environmental factors, such as free radical. The use of antioxidant and anti-collagenase to prevent the aging proses has been known. Natural compounds from plants are one of the sources of antioxidant and anti-collagenase that has ability to prevent aging. Genistein and Epicatechin are the major phenolic compound found in G. max. Objectives: This research was to evaluate the antiaging potential of genistein and epicatechin through antioxidant activity assay (ABTS-reducing activity assay) and collagenase inhibitory activity assay. Methods: Antioxidant analysis of Genistein and Epicatechin was performed by 2,2’- azinobis-3-ethylbenzo-thiazoline-6-sulfonic acid (ABTS) reducing activity Assay. Antiaging assay was conducted through inhibitory of collagenase, one of important enzyme in aging process. Results: ABTS- reducing activity assay showed that both compounds had great ABTS-reducing activity in which epicatechin had better activity than genistein. Epicatechin had low value of IC50 ABTS-reducing activity around 14.39 µg/ml better than genistein with IC50 about 43.17 µg/ml. In terms of collagenase inhibitory activity assay, epicatechin had lower value of IC50 (9.08+-3.46 ug/ml), better than genistein (98.74+-4.25 ug/ml). Conclusion: Epicatechin had higher antioxidant and anti- collagenase activity compared to Genistein.